Analisis Performa Pegas Kopling Original Dengan Pegas Kopling TDR Racing Pada Motor Menggunakan Metode Software Stress Analisis - Andriyansah; Oscar Haris (Universitas Nusa Putra, 2021)
The clutch spring (spring compression) serves to press the pressure plate so that the clutch lining is close to the clutch plate, so that the clutch does not slip. In addition, the clutch spring also functions to relieve the pressure between the clutch lining and the clutch plate. The force or load applied to the original spring is 2.02 N, and the force applied to the TDR spring is 2.5 N. Load analysis to determine stress and strain using Autodesk inventor software. The simulation results can be concluded that the stress (Stress) that occurs in the standard spring is the largest (Maximum Stress) occurs in the YY vector direction with a value of 37.56 MPa, and the smallest stress (Minimum Stress) occurs in the YY vector direction with value -57.21 MPa. While the stress that occurs in the TDR spring is the largest (Maximum Stress) in the direction of the YY vector with a value of 33.49 MPa, and the smallest stress (Minimum Stress) occurs in the direction of the YY vector with a value of -31.22 MPa. The largest strain (Maximum Strain) occurs in the YY vector direction with a value of 2.45 ul, and the smallest stress (Minimum Strain) occurs in the YY vector direction with a value of -3.61 ul . While the strain (Strain) that occurs in the TDR spring is the largest (Maximum Strain) occurs in the direction of the YZ vector with a value of 1.757 ul, and the smallest stress (Strain) (Minimum Strain) occurs in the direction of the YY vector with a value of -1.863 ul.